1996
DOI: 10.1111/j.1651-2227.1996.tb14282.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of intrauterine growth retardation

Abstract: This review focuses on intrauterine growth retardation (IUGR) occurring spontaneously and without a defined infective, toxic or genetic cause. Such fetal growth retardation is generally thought to be a consequence of inadequate provision of nutritional substrates across the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
0
23
0
3
Order By: Relevance
“…High insulin levels could, later in life, stimulate early secretion of luteinizing hormone, leading to early puberty (2,28,29). Nevertheless, in most of the children born SGA in our sample, the course and timing of puberty were within the normal range.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…High insulin levels could, later in life, stimulate early secretion of luteinizing hormone, leading to early puberty (2,28,29). Nevertheless, in most of the children born SGA in our sample, the course and timing of puberty were within the normal range.…”
Section: Discussionmentioning
confidence: 83%
“…These are also maintained postnatally (1,2) and may affect the long-term pattern of postnatal growth and development. A number of longitudinal studies have shown that although the majority of children born small for gestational age (SGA) exhibit significant catch-up growth during the first 6-12 months of life, about 10 -17% do not.…”
Section: Introductionmentioning
confidence: 99%
“…Programming of the endocrine mechanisms of foetal growth which are mediated by insulin and insulin like growth factors (IGF) have been implicated. 20 In our sample population, we have previously reported an Abdominal fat and birth size in children SP Garnett et al inverse relation between IGF-I concentrations at age 7=8 y and birth size -children with the lowest birth size and heaviest current weight had the highest IGF-I concentrations. 21 High concentrations may reflect persisting IGF-I resistance or alternatively be a response to adequate postnatal nutrition and hence be a feature of rapid postnatal growth.…”
Section: Discussionmentioning
confidence: 96%
“…This system consisted of a To verify the specificity of the changes in the PeN, the number of grains in SS mRNA-expressing neurons in the cortex of adult rats was also analyzed. From each animal, a total of 100 cortical cells, divided over five to eight slides, were analyzed at the level of bregma Ϫ0.26 mm to Ϫ1.80 mm (14). Cells were considered labeled when the number of silver grains overlying the cytoplasm were greater than 10 times the background levels.…”
Section: Methodsmentioning
confidence: 99%